A Questionnaire Based Survey with Physicians for Effectiveness and Tolerability of Secnidazole in Periodontitis at Sri Lanka - Senanayake, Asanka; Pawar, Dilip; Shinde, Amol (British Journal of Healthcare and Medical Research, 2022)
Background: Periodontitis is a chronic inflammatory disease affecting supportive gingival tissue. Since most of periodontal infections causes orofacial infections, the prescribing of antimicrobials by physician has become important in dental practice. Antimicrobials are the mainstay of the treatment of periodontitis. Objective: To conduct questionnaire-based survey among physicians in Sri Lanka for the effectiveness and tolerability of secnidazole in periodontitis. Methodology: A prospective observational study was conducted for six months with physicians based in Sri Lanka. A questionnaire was prepared in consultation with key opinion leaders, including ten questions which focused on effectiveness and tolerability of 2gm secnidazole in patients with periodontitis. Physician’s voluntary consent was taken for their participation in the survey. Results: A total of forty-one responses were received from physicians, it was observed that 90.2% physicians prescribed antibacterial followed by antiprotozoal in dental infections. Most common symptom for the prescription of secnidazole was in periodontal pus 53.7% accompanied by inflammatory symptoms 46.3%, and bleeding gums. Secnidazole 2gm single dose was preferred by 87.8% physicians for its convenient dosing over the metronidazole, tinidazole and ornidazole. Physicians found secnidazole was good to excellent for effectiveness in 97.6% and tolerability in 97.6% for periodontitis. Conclusion: Secnidazole 2gm single dose was found effective and tolerable in the treatment of periodontitis. It is preferred over the other nitroimidazole drugs like metronidazole, tinidazole and ornidazole for its convenient dosing. From the survey it is observed that, physicians were in favor of Secnidazole for treatment of periodontitis.